Leaning Over the Fence: Heritage Fair Projects as ‘Funds of Knowledge’ - Wiltse, Lynne (Alberta Journal of Educational Research, 2015)
This paper is a response to an article, “Creepy White Gaze: Rethinking the Diorama as a Pedagogical Activity” (Sterzuk & Mulholland, 2011), published in the Alberta Journal of Educational Research, in which Sterzuk and Mulholland critiqued a heritage fair entry, “Great Plains Indians.” I report on a school-university collaborative research project that examined the ways in which out-of-school practices and knowledges of Canadian Aboriginal students might provide these students with access to school literacy practices. Grounded in a ‘funds of knowledge’ approach, this paper presents an alternative reading, explaining how students’ linguistic and cultural resources from home and community networks were utilized to reshape school literacy practices through their involvement in a heritage fair program. Cet article est une réponse à un autre intitulé “Creepy White Gaze: Rethinking the Diorama as a Pedagogical Activity” (Sterzuk & Mulholland, 2011), publié dans la revue Alberta Journal of Educational Research et dans lequel les auteurs ont critiqué une soumission, « Great Plains Indians » (Indiens des grandes plaines), à une fête du patrimoine. Je fais état d’un projet de recherche collaboratif (école-université) qui a examiné les façons dont les pratiques et les connaissances en dehors du contexte scolaire d’élèves autochtones canadiens pourraient leur faciliter l’accès à des pratiques scolaires en matière d’alphabétisation. Reposant sur une approche « fonds de connaissance », cet article présente une autre interprétation et explique dans quelle mesure les ressources linguistiques et culturelles acquises par les élèves à la maison et dans la communauté ont servi à remanier les pratiques scolaires en matière d’alphabétisation par le biais de leur participation à un programme des fêtes du patrimoine.